2021
DOI: 10.3389/fmars.2021.685429
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Immunity, and Transcriptome Response to Dietary Wnt/β-Catenin Pathway Activator TWS119 in Penaeus vannamei

Abstract: Wnt/β-catenin signalling plays an essential role in the immunity of Penaeus vannamei. In this study, the effects of dietary Wnt/β-catenin pathway activator TWS119 on the growth, immunity, and transcriptome response in P. vannamei were investigated. Penaeus vannamei were fed diets with added TWS119 at doses of 0 (T0), 0.25 (T0.25), 1 (T1), 4 (T4), 16 (T16), or 64 mg·kg−1 (T64), respectively. LvGSK3β activity was effectively inhibited in P. vannamei given TWS119. The growth of P. vannamei in the T16 group was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Transcriptome sequencing, a common tool in biology research at present, is also extensively used to analyses the mechanisms associated with protein source substitution in diets on the growth, metabolism and immunity of organisms [ 21 , 34 , 35 ]. In the present study, a comparative transcriptome analysis of L. vannamei containing the CPC and FM groups was performed to investigate the mechanism of the effect of the CPC substitution for fishmeal.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Transcriptome sequencing, a common tool in biology research at present, is also extensively used to analyses the mechanisms associated with protein source substitution in diets on the growth, metabolism and immunity of organisms [ 21 , 34 , 35 ]. In the present study, a comparative transcriptome analysis of L. vannamei containing the CPC and FM groups was performed to investigate the mechanism of the effect of the CPC substitution for fishmeal.…”
Section: Discussionmentioning
confidence: 99%
“…Hemolymph from another three shrimp randomly selected from each tank was withdrawn into modified ACD anticoagulant solution and centrifuged for 5 min (3000× g at 4 °C) to isolate hemocytes, using as a sample. The hemocytes were stored at −80 °C for RNA extraction and used for the detection of gene expression and transcriptomic analysis, as our previous study showed [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations